Mine Slope Stability Analysis CV. Putra Idola Against the Padang-Painan Cross Road with GSI Method and Rock Mass Rating - Aditya, Fariz; Heriyadi, Bambang; Saldy, Tri Gamela; Nauli, Fitri; Yanti, Syari Rahma; Marlina, Riam; Putra, Kyrie Eleison; Algozi, Rahmad; Akmal, Muhammad (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
A slope is a sloping part of the ground surface that connects the higher areas with the lower areas. Slope stability relies heavily on rock mass characteristics, including the Rock Mass Rating (RMR) and Geological Strength Index (GSI) classifications, which are used to evaluate rock quality and slope stability. This research was conducted at the mine CV. Putra Idola which is located in Teluk Kabung Tengah Village, Bungus Teluk Kabung District, Padang City and Nagari Siguntur, XI Koto Tarusan District, Pesisir Selatan Regency, West Sumatra Province. The goal is to determine RMR and GSI values and identify potential slope instability. The methods used include geotechnical mapping with a 15.2-meter long scanline technique to identify burly structures as well as laboratory testing to obtain the physical and mechanical properties of rocks. The data obtained were analyzed to calculate the RMR and GSI values of different types of rocks at the research site. The results showed that the GSI values on the three slopes studied ranged from 53 to 75, while the RMR values ranged from 57 to 75. Based on this classification, the Fresh Andesite and Hornfels rocks are included in the